MTAD combined with endosonic irrigation as a new approach for the disinfection of Enterococcus faecalis biofilm - Lei Lei; Hongyan Liu; Yanling Cai; Xi Wei (Elsevier, 2015)
Background/purpose: Enterococcus faecalis plays a major role in continuing refractory apical periodontitis. The purpose of this study was to investigate the antibacterial effects of sodium hypochlorite (NaOCl) combined with MTAD [a mixture of tetracycline isomer (doxycycline), an acid (citric acid), and a detergent (Tween 80)] as an endosonic irrigation protocol against E. faecalis biofilm. Materials and methods: The dentin blocks were incubated with E. faecalis and randomly assigned to five irrigation groups (n = 10): MTAD, 1.3% NaOCl with MTAD, 1.3% NaOCl, 5.3% NaOCl, and 5.3% NaOCl with 17% EDTA using Endoactivator oscillation for 30 seconds and 1 minute, respectively; saline without agitation as a control. The bacterial samples were measured by colony-forming counting. The percentage of viable cells and the thickness of the biofilms were evaluated using confocal laser scanning microscopy. Specimens were observed via scanning electron microscopy. Results: When Endoactivator was applied for 30 seconds, viable counting of the 5.3% NaOCl/17% EDTA group and 1.3% NaOCl/MTAD group were lower than the MTAD group (P < 0.05), whereas the differences between the former two are not significant. There were no statistically significant differences in the number of colony-forming counting unit between 30 seconds and 60 seconds (P > 0.05). The 1.3% NaOCl/MTAD group and the MTAD group appeared to preserve the structure of the dentin surface and cause efficient removal of the smear layer. Conclusion: Endoactivator could improve the synergistic antimicrobial action of 1.3% NaOCl and MTAD against E. faecalis biofilm and removal of the smear layer with less erosion of the dentin surface. The combination could be a safe and efficient irrigation regimen.